Staying Into Religious Boundaries and Bearing Polygamy: Understanding Jealousy, Marital Satisfaction, and Mental Health among Muslim Women (Al-Qamar, 2021)
In Islamic culture, women are bound to accept more than one and up to four marriages of their husbands and this sharing may appear as a threat to them. The present study aimed to examine the jealousy, marital satisfaction, and mental health in a purposive sample of 192 women in polygamous marriages (first and second wives) with an age range of first wives 25-60 (M = 40.30, SD =7.86) and second wives 18-40 (M = 26.60, SD =7.41). The sample was drawn from Punjab. It was Correlational research with a cross-sectional design. Revised Dyadic Adjustment Scale[i]and Mental Health Inventory[ii] along with the newly developed indigenous Jealousy Scale for polygamous women[iii] were used as measures. Results revealed men's injustice and biased behavior toward their multiple wives cause jealousy and poor marital satisfaction in polygamous women which deteriorate their mental health. Findings showed that poor marital satisfaction mediated between jealousy and mental health (Psychological well-being and psychological distress). After controlling the poor marital satisfaction, jealousy significantly negatively predicted Mental Health (Psychological well-being) and positively predicted psychological distress but reduces the value which indicates partial mediation. The Implications of the findings were discussed for family settings, family therapists, and law advisors in the Pakistani socio-cultural context and wherever polygamy is allowed in the world. The study is also implemented to seek the original teachings and true picture of Islamic perspectives about polygamy.
Keywords: Jealousy; Marital Satisfaction; and Mental Health; Polygamous women